THE USE OF MULTIMEDIA PRESETATIONS IN TEACHING THE COURSE «LINGUISTIC COUNTRYSTUDY IN TOURISM BUSINESS» - Старинець, О. А. (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2014)
The article gives the analysis of substantiation and ways of usage of multimedia presentations in teaching the course «Linguistic country study in tourism business», the stages of multimedia presentation preparation and principles of choosing materials are given